The boundary stone between Aquileia and Emona - Šašel Kos, Marjeta (Arheološki vestnik, 2002)
In the summer of 2001, a boundary stone between Aquileia and Emona, made of Aurisina/Nabrežina limestone, was discovered in the bed of the Ljubljanica River below Bevke, some 13 km to the southwest of Ljubljana. It is most probably dated to the Augustan period and is certainly pre-Claudian. According to other similar boundary stones, neither of the two communities involved could be subordinate to the other and both belonged to the same administrative unit. This means that both towns belonged to Italy and that Emona had never been part of Illyricum (or, later, of the province of Pannonia).